Egy itáliai krónika interpretációs lehetőségei: a magyar hadi vezetők Domenico da Gravina krónikájában - Virágh, Ágnes (Hallgatói Műhelytanulmányok, 2022)
Virágh, Ágnes: Possible interpretations of an italian chronicle: Hungarian military leaders in the chronicle of Domenico da Gravina This work examines what Domenico da Gravina’s attitude was towards the Hungarians fighting in the Kingdom of Naples. The analysis is based on the Chronicon de rebus in Apulia gestis, in which several Hungarian military leaders are presented. The following observations were made from the results: since Domenico knew the military leaders personally, his reports were much more detailed than those of the other chroniclers. He admired Stephen Lackfi, the Voivode of Transylvania the most. He commemorated his speech at the army muster, his mercy, his excellent strategic sense and the case when Louis of Taranto challenged Lackfi to a duel. Besides Lackfi, he praised the merits of John Csuz, whom he referred to as an expert in military action. Hungarians were regarded to be persistent warriors by him, who despite the hardships, successively defended the castles entrusted to them. He highlights the battlefield value of the Hungarian archery divisions and compares them with the Neapolitan cavalry that always suffered defeat in combat.